2020
DOI: 10.24310/mgnmar.v1i2.8457
|View full text |Cite
|
Sign up to set email alerts
|

El valor del lugar en las relaciones de inclusión y exclusión en un colegio rural agrupado. Un estudio etnográfico

Abstract: En un contexto marcado por la transformación neoliberal de los servicios educativos y cuando la inclusión se presenta como un valor de referencia para el desarrollo sostenible, la finalidad de este artículo es contribuir a la comprensión del papel activo que juegan los lugares y las interacciones que se generan en ellos para la formación de experiencias de segregación o de inclusión en el entorno de la escuela rural. El objetivo es identificar cuáles son las experiencias de inclusión o exclusión entre los miem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This metrocentric vision has an influence on how rural schools are defined and understood (Gristy et al, 2020). Traditionally, they have been not only defined, but also organised, from an urban perspective through the creation of 'clusters' or 'grouped schools' -organisational systems that allow for the extrapolation of urban organisation to the rural environment (Hargreaves, 2017;Matías Solanilla & Vigo-Arrazola, 2020). In several countries in the study carried out by Hargreaves et al (2009), it can be observed that there is a persistent political bias towards rural schools, due to a predominantly restrictive and centrist perspective, that causes education to be defined and categorised depending on its territorial location and from the classic characteristics and formats derived from the school with students organised into grades based on age or level (Uttech, 2001).…”
Section: Rural Schools: Policies and Discoursesmentioning
confidence: 99%
See 1 more Smart Citation
“…This metrocentric vision has an influence on how rural schools are defined and understood (Gristy et al, 2020). Traditionally, they have been not only defined, but also organised, from an urban perspective through the creation of 'clusters' or 'grouped schools' -organisational systems that allow for the extrapolation of urban organisation to the rural environment (Hargreaves, 2017;Matías Solanilla & Vigo-Arrazola, 2020). In several countries in the study carried out by Hargreaves et al (2009), it can be observed that there is a persistent political bias towards rural schools, due to a predominantly restrictive and centrist perspective, that causes education to be defined and categorised depending on its territorial location and from the classic characteristics and formats derived from the school with students organised into grades based on age or level (Uttech, 2001).…”
Section: Rural Schools: Policies and Discoursesmentioning
confidence: 99%
“…The space where community evolves at different levels-social, economic and cultural-is referred to as territory (Massey, 2012). The decisions taken by the governments, national and local, jeopardise the sustainability the rural territories by promoting an exodus to urban areas (Lethonen, 2021) indirectly causing the closure of schools, which is an international trend (Autti & Hyry-Beihammer, 2014;Cedering & Wihlborg, 2020;Matías Solanilla & Vigo-Arrazola, 2020;Villa & Knutas, 2020) and a factor for depopulation (Lethonen, 2021). School closure often includes discussions and debates about the function of the school, the meaning of the school, and the future of the local community (Villa & Knutas, 2020) and forces local communities throughout Europe to fight for their schools (Amcoff, 2012).…”
Section: Introduction and Research Significancementioning
confidence: 99%